Therapeutic potential of the dual peroxisome proliferator activated receptor (PPAR)α/γ agonist aleglitazar in attenuating TNF-α-mediated inflammation and insulin resistance in human adipocytes. (May 2016) - Massaro, Marika; Scoditti, Egeria; Pellegrino, Mariangela; Carluccio, Maria Annunziata; Calabriso, Nadia; Wabitsch, Martin; Storelli, Carlo; Wright, Matthew; De Caterina, Raffaele
Graphical abstract: Abstract: Adipose tissue inflammation is a mechanistic link between obesity and its related sequelae, including insulin resistance and type 2 diabetes. Dual ligands of peroxisome proliferator activated receptor (PPAR)α and γ, combining in a single molecule the metabolic and inflammatory-regulatory properties of α and γ agonists, have been proposed as a promising therapeutic strategy to antagonize adipose tissue inflammation. Here we investigated the effects of the dual PPARα/γ agonist aleglitazar on human adipocytes challenged with inflammatory stimuli. Human Simpson-Golabi-Behmel syndrome (SGBS) adipocytes were treated with aleglitazar or ⿿ for comparison ⿿ the selective agonists for PPARα or γ fenofibrate or rosiglitazone, respectively, for 24 h before stimulation with TNF-α. Aleglitazar, at concentrations as low as 10 nmol/L, providing the half-maximal transcriptional activation of both PPARα and PPARγ, reduced the stimulated expression of several pro-inflammatory mediators including interleukin (IL)-6, the chemokine CXC-L10, and monocyte chemoattractant protein (MCP)-1. Correspondingly, media from adipocytes treated with aleglitazar reduced monocyte migration, consistent with suppression of MCP-1 secretion. Under the same conditions, aleglitazar also reversed the TNF-α-mediated suppression of insulin-stimulated ser473 Akt phosphorylation and decreased the TNF-α-induced ser312 IRS1 phosphorylation, two major switches in insulin-mediated metabolic activities, restoring glucose uptake in insulin-resistant adipocytes. Such effects were similar to those obtainable with a combination of single PPARα and γ agonists. In conclusion, aleglitazar reduces inflammatory activation and dysfunction in insulin signaling in activated adipocytes, properties that may benefit diabetic and obese patients. The effect of aleglitazar was consistent with dual PPARα and γ agonism, but with no evidence of synergism.